Epidemiological and molecular characteristics of extraintestinal pathogenic escherichia coli isolated from diseased cattle and sheep in Xinjiang, China from 2015 to 2019 - Xiaoxiao Gu; Qin Wu; Yingjin Chai; Xin Huang; Xia Zhou; Mengli Han; Tongzhong Wu; Xingxing Zhang; Fagang Zhong (BMC Veterinary Research)
Abstract Escherichia coli has become a common causative agent of infections in animals, inflicting serious economic losses on livestock production and posing a threat to public health. Escherichia coli infection is common and tends to be complex in Xinjiang, a major region of cattle and sheep breeding in China. This study aims to explore the current status and molecular characteristics of Escherichia coli infection in cattle and sheep in Xinjiang, as part of the disease prevention and control strategy. Herein we isolated Extraintestinal pathogenic Escherichia coli (ExPEC) from the liver, spleen, lung, heart, and lymph nodes of infected cattle and sheep (Xinjiang, China), and phylogenetic grouping, serotyping, and multilocus sequence typing were performed to determine epidemic and molecular characteristics. We also assessed their biofilm formation ability. A total of 132 strains of ExPEC were identified from diseased cattle and sheep, belonging to 7 phylogenetic groups. A and B1 are advantageous groups. Further, 22 serogroups were found, with O101 (26/132), O154 (14/132), and O65 (8/132) being the predominant ones. Among the seven sequence types identified by multilocus sequence typing, ST10 was the most common, followed by ST23 and ST457. Of 132, 105 (79.5%) strains were able to form biofilms: 15 strains (11.4%) were strong, 28 (21.2%) were medium, and 62 (47%) were weak biofilm producers. These findings will contribute to a better understanding of the molecular epidemiology of ExPEC in Xinjiang, China, and can be applied to the development, prevention, and disease control of future diagnostic tools and vaccine.